The influence of pairing correlations on the isospin symmetry breaking corrections of superallowed Fermi beta decays - Çalık A.E.; Gerçeklioğlu M.; Selam C. (Maik Nauka-Interperiodica Publishing, 2013)
Within the framework of quasi-particle random phase approximation, the isospin breaking correction of superallowed 0 + ? 0 + beta decay and unitarity of Cabibbo-Kobayashi-Maskawa mixing matrix have been investigated. The broken isotopic symmetry of nuclear part of Hamiltonian has been restored by Pyatov's method. The isospin symmetry breaking correction with pairing correlations has been compared with the previous results without pairing. The effect of pairing interactions has been examined for nine superallowed Fermi beta decays; their parent nuclei are 26 Al, 34 Cl, 38 K, 42 Sc, 46 V, 50 Mn, 54 Co, 62 Ga, 74 Rb. © 2013 Pleiades Publishing, Ltd.